ANTI STRESS EFFECT OF ASHWAGANDHA (WITHANIA SOMNIFERA) WILD AND CULTIVATED VARIETIES ON WORK RELATED PROFESSIONALS - Arvind Kumar Mishra; S. Pavan Kumar; M. Paramkussh Rao (AYUSHDHARA, 2020)
Manas is the controller of Indriyas and the activities of Manas are the direct outcome of cerebral functions. There are three major Universal attributes (Mahagunas) of Manas namely Sattva, Rajas and Tamas. The variations in inter- individual as well as intra-individual leads to psychic behaviour. A study was conducted of Chittodvega anti-stress effect of Ashwagandha varieties on work related professionals. The study was conducted on 60 volunteers taken from T.T.D’s printing press, Tirupati. After screening, the selected volunteers were assigned three groups containing 20 patients each. The first and second groups served as the trial groups (I Group –WSN, II Group– WSWM) and third group (III Group - PG) served as the placebo control. Pre- Treatment and Post- treatment readings were recorded to assess various parameters of this study. Group I- Ashwagandha Nagori with milk (WSN) Group II– Ashwagandha wild with milk (WSWM) in a dose of 1gm were administered orally. The duration of the treatment was 40 days. Wheat powder placebo was given along with milk. Ashwagandha churna along with milk (WSN-Group I) and Ashwagandha churna purified with milk steam (WSWM -Group II) are taken as the test drugs and compared with the placebo group III. There is significant difference is observed in Group 2 better in headache, trembling of lips, neck & back pain, low sexual drive, diarrhoea, feeling of loneliness, reduced work productivity, frequent use of counter drugs, increased smoking and alcohol, sudden attacks of panic, frequent urination, excess anxiety, increased anger, depression, insomnia, difficulty concentration than Group 1. There is significant difference is observed in frequent sweating, dry mouth, and difficulty in making decision and weight gain or weight loss in Group 1 than Group 2.